READING PROFICIENCY AND COGNITIVE READING STRATEGIES THROUGH ONLINE DYNAMIC ASSESSMENT (ODA) IN ENGLISH FOR ECONOMY - Imron, Ahmad; Anwar, Khoirul (English Review: Journal of English Education, 2024)
Dynamic Assessment (DA) can help EFL students use more cognitive reading skills, but its application in ESP learning is restricted. DA in ESP is an important research subject since reading comprehension is an essential skill for English for Specific Purposes (ESP) students. The purpose of this study is to look into the impact of online DA on reading ability and the usage of cognitive reading comprehension strategies among English for Economy learners. The study employs a quantitative experimental design and survey, with two groups of management students (30 in the experimental class and 30 in the control class) currently enrolled in the English for Economy program, which includes planned and scheduled online dynamic assessments. The study found that the Online Dynamic Assessment-supported ESP reading program considerably improves management students' reading abilities, as shown by the experimental group's higher posttest performance and significant t-test results. The large range and standard deviation in the experimental group demonstrate the exam's capacity to discern between different student competencies. Furthermore, the study reveals students' proactive role in improving their comprehension and recall by detailing their cognitive reading strategies at various reading stages, including pre-reading anticipation and skimming, in-reading context-based inference, and post-reading categorization and content review. To improve ESP outcomes, future research should incorporate bigger sample sizes, a variety of ESP domains, motivating factors, strategy analysis, technique comparisons, proficiency adjustments, and skill integrations.